Water Quality Assessments for Urban Water Environment - Kumar, Pankaj (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This special issue entitled "Water Quality Assessments for Urban Water Environment," strives to highlights the status quo of water environment, opportunities and challenges for their sustainable management in lieu of rapid global changes (land us eland cover changes, climate change, population growth, change in socio-economic dimension, urbanization etc.), in the urban space particularly in developing nations around the world. It also highlights the effect of COVID19 pandemic on water resources and way forward to minimize the risk of spreading health risk associated with wastewater management. Considering the complex nature of the urban water security, it highlights the importance of emerging approaches like socio-hydrology, landscape ecology, regional-circular-ecological sphere etc., which presents a perfect combination of hard (infrastructure) and soft (numerical simulations, spatial technologies, participatory approaches, indigenous knowledge) measures, as the potential solutions to manage this precious water resource in coming future. Finally, what is the way forward to enhance science-policy interface in a better way to achieve global goals e.g., SDGs at local level in a timely manner. It provides valuable information about sustainable water resource management at the urban landscape, which is very much useful for policy-makers, decision-makers, local communities, and other relevant stakeholders.